MODERN AND INNOVATIVE PEDAGOGICAL TECHNOLOGIES OF TEACHING READING TO B1 LEVEL LEARNERS (Journal of Science-Innovative Research in Uzbekistan, 2025)
The article examines modern and innovative pedagogical technologies for teaching reading to B1 level English learners. It evaluates methods such as the communicative approach, flipped classroom, task-based learning, and the use of digital tools. The paper highlights key aspects that contribute to increasing student motivation and developing their critical thinking and reading competence.